2016
DOI: 10.1515/pjst-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Causal Attributions of Success and Failure and Mood States in Football Players

Abstract: Introduction. The aim of the study was to determine the causal attributions of success and failure in a football match in a group of football players, as well as to investigate the association of the players' attributions with their level of achievement and the relationships between their causal attributions and affective states. Material and methods. The study involved 75 football players, including 44 players from the first league and 31 players from the third league. The research was carried out using the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Previous research about academic examinations (Cortés-Suárez and Sandiford, 2008) has observed that students often attributed failures to factors and circumstances, which were outside their control such as better performance of contestants, lack of luck and the behaviour of teachers. Whereas research in the field of sports revealed that participants who had been successful in competitions made internal attributions more than others who were unsuccessful (Szczepaniak and Guszkowska, 2016). Weiner (1986) suggests that the effort students put into their academic work can be explained by how they perceive their successes and failures.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous research about academic examinations (Cortés-Suárez and Sandiford, 2008) has observed that students often attributed failures to factors and circumstances, which were outside their control such as better performance of contestants, lack of luck and the behaviour of teachers. Whereas research in the field of sports revealed that participants who had been successful in competitions made internal attributions more than others who were unsuccessful (Szczepaniak and Guszkowska, 2016). Weiner (1986) suggests that the effort students put into their academic work can be explained by how they perceive their successes and failures.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is unclear why this null relationship took place since the few previous studies that have analyzed the individual consequences of the team's vulnerability did not find a similar result. However, one could speculate that this may be because players often have an external causality locus (i.e., each player could attribute to external reasons the team's vulnerability under pressure), and it is difficult to acknowledge that IP has dropped in situations where the team had no resources to face adversity 39 . That is, to accept a decline in IP in the face of adverse situations implies taking on some of the responsibility for the lack of resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, one could speculate that this may be because players often have an external causality locus (i.e., each player could attribute to external reasons the team's vulnerability under pressure), and it is difficult to acknowledge that IP has dropped in situations where the team had no resources to face adversity. 39 That is, to accept a decline in IP in the face of adverse situations implies taking on some of the responsibility for the lack of resources. However, this reasoning is speculative; thus, determining whether there is indeed a significant (negative) relationship or not between VP and IP (and why) warrants further investigation.…”
Section: Relationships Between Vulnerability Under Pressure and Subje...mentioning
confidence: 99%